CSIG-05. DISSOCIATION OF THE INTRAMOLECULARLY CLEAVED N- AND C-TERMINAL FRAGMENTS OF ADHESION G PROTEIN-COUPLED RECEPTOR GPR133 (ADGRD1) INCREASES ITS CANONICAL SIGNALING IN GLIOBLASTOMA. (12th November 2021) - Frenster, Joshua; Stephan, Gabriele; Ravn-Boess, Niklas; Bready, Devin; Wilcox, Jordan; Liebscher, Ines; Schöneberg, Torsten; Placantonakis, Dimitris
Abstract: We previously demonstrated that GPR133 (ADGRD1), an adhesion GPCR that signals via cytosolic cAMP increase, is de novo expressed in glioblastoma (GBM) and enriched in patient-derived glioblastoma stem cells. Knockdown of GPR133 reduces GBM cell proliferation and tumorsphere formation, and abolishes orthotopic xenograft initiation in vivo . GPR133's requirement for GBM growth and its absence in non-malignant brain suggest its therapeutic potential, yet its mechanisms of action and activation remained unclear. Here, we demonstrate in patient-derived GBM cultures and HEK293T cells that GPR133 gets intramolecularly cleaved into N-terminal and C-terminal fragments (NTF and CTF) right after synthesis in the endoplasmic reticulum. The resulting NTF and CTF remain non-covalently bound to each other, until the mature receptor reaches the plasma membrane, where we observe dissociation of the extracellular NTF from the transmembrane-spanning CTF. While cleavage is not required for correct subcellular trafficking, the cleaved wild-type GPR133 generates significantly higher cytosolic cAMP levels than an uncleavable point mutant GPR133 (H543R), suggesting that cleavage and dissociation are involved in receptor activation. To test this hypothesis in a more controllable proxy system, we generated a fusion of the CTF of GPR133 and the N-terminus of human protease-activated receptor 1 (hPAR1). Indeed, acute thrombin-induced cleavage and shedding of the hPAR1 NTF increases intracellular cAMP levels generated by the GPR133 CTF. These results support a model wherein dissociation of the NTF from the CTF at the plasma membrane promotes GPR133 activation and downstream signaling. To test whether extracellular binding proteins could influence NTF shedding and/or GPR133 signaling activation, we conducted ligand discovery screens and indeed found a new GPR133 binding protein in GBM cells, which is capable of influencing receptor signaling. Together, these findings provide critical insights into GPR133's mechanism of activation, that will guide future approaches of therapeutic targeting of GPR133 in GBM.